Investigation of converter losses using a first prototype of Silicon - Ahmad, Amer; Bergman, Niclas (My University, 2007)
In this thesis work, a 600 / 28V full-bridge converter is investigated regarding its efficiency. Moreover, a purpose was also to implement a first SiC BJT prototype into a simulation set-up in order to study if the existing data and model set-up was sufficient for accurate dynamic modelling. The focus was put on comparing the losses of the SiC BJT prototype with that of a classical IGBT in a full-bridge application An equivalent transistor model of a classical MOSFET has been programmed in Matlab with the objective to achieve estimations of switching and conduction losses. Due to the complex nature of the SiC BJT it was not possible to achieve realistic loss estimations of this transistor. Lack of sufficient data based on measurements of this first SiC BJT prototype also contributed to the fact that these simulation results were not sufficient. Measurements have been available only for lower voltage and current levels at turn-on and turn-off for the SiC BJT. To achieve an estimation of the switching losses, the measured results of the SiC transistor have been scaled to the voltage and current levels applied in this DC/DC converter application. Calculations of losses in the transformer and filter inductor of the DC/DC converter have also been made. The conclusion that can be drawn from this thesis work is that this promising SiC BJT prototype, with accordingly high losses, still is at an early stage and more investigations need to be conducted.
Keywords: Elkraftteknik; Electric power engineering